Co-bedding of Preterm Newborn Pigs Reduces Necrotizing Enterocolitis Incidence Independent of Vital Functions and Cortisol Levels - Brunse, Anders; Peng, Yueming; Li, Yanqi; Lykkesfeldt, Jens; Sangild, Per Torp (Frontiers in Pediatrics, 2021)
Background. Preterm infants are born with immature organs, leading to morbidities such as necrotizing enterocolitis (NEC), a gut inflammatory disease associated with adverse feeding responses but also hemodynamic and respiratory instability. Skin-to-skin contact including ’kangaroo care’ may improve infant survival and health via improved vital functions (e.g. pulmonary, cardiovascular) and endocrine influences by adrenal glucocorticoids. Clinical effects of skin-to-skin contact for newborn siblings (‘co-bedding’) are not known. Using NEC-susceptible preterm pigs as models, we hypothesized that co-bedding and exogenous glucocorticoids improve vital functions and NEC resistance. Methods. In experiment 1, caesarean-delivered, formula-fed preterm pigs were reared in incubators with (co-bedding, COB, n=30) or without (single-bedding, SIN, n=29) a sibling until euthanasia and tissue collection on day four. In experiment 2, single-bedded preterm pigs were treated postnatally with a tapering dose of hydrocortisone (HC, n=19, 1-3 mg/kg/d) or saline (CON, n=19). Results. Co-bedding reduced NEC incidence (38 vs. 65%, p<0.05) and increased the density of colonic goblet cells (+20%, p<0.05) but had no effect on pulmonary and cardiovascular functions (respiration, blood pressure, heart rate, blood gases) or cortisol levels. There were limited differences in intestinal villous architecture and digestive enzyme activities. In experiment 2, HC treatment increased NEC lesions in the small intestine without any effects on pulmonary or cardiovascular functions. Conclusion. Co-bedding may improve gut function and NEC resistance independently of cardiorespiratory function and cortisol levels, but pharmacological cortisol treatment predispose to NEC. Preterm pigs may be a useful tool to better understand the physiological effects of co-bedding, neonatal stressors and their possible interactions with morbidities in preterm neonates.